2017
DOI: 10.22146/jsv.22824
|View full text |Cite
|
Sign up to set email alerts
|

Daya Hidup Spermatozoa Epididimis Kambing Peranakan Ettawa yang Dipreservasi dengan Pengencer Tris dan Bberbagai Konsentrasi Maltosa

Abstract: Cauda epididymal spermatozoa could be used as an alternative source of gamete in the application of various reproductive technologies, since the spermatozoa is motile and has ability for fertilizing the oocyte. Theobjective of this research was to examine the effectivity of maltose in maintaining viability of ettawa crossbreed goat epididymal spermatozoa preserved at 3–5oC. Five testis with epididymides of ettawa crossbreed goat were obtained from slaughterhouse. Epididymal spermatozoa was collected by the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…However, semen volume in this study was lower than that reported by three previous studies, which were 1.54±0.32 ml , 2.64 ml (Pratiwi, 2007) and 2.44 ml (Armansyah et al, 2018). The reported value of the semen volume is still within the normal range of goat semen as written by some researchers, such as 0.96 ml/ejaculate (Putranti et al,2020), 0.70-1.50 ml (Suyadi et al, 2004), 0.640 (Rizal M., 2009) and 0.80 ml (Pamungkas et al, 2008). Different volumes among studies would be affected by the number of factors such as the frequency of ejaculation and variance of individual livestock breeds, age, season, libido, and the variation in the condition of livestock (LukmanHy et al, 2022b).…”
Section: Resultscontrasting
confidence: 66%
“…However, semen volume in this study was lower than that reported by three previous studies, which were 1.54±0.32 ml , 2.64 ml (Pratiwi, 2007) and 2.44 ml (Armansyah et al, 2018). The reported value of the semen volume is still within the normal range of goat semen as written by some researchers, such as 0.96 ml/ejaculate (Putranti et al,2020), 0.70-1.50 ml (Suyadi et al, 2004), 0.640 (Rizal M., 2009) and 0.80 ml (Pamungkas et al, 2008). Different volumes among studies would be affected by the number of factors such as the frequency of ejaculation and variance of individual livestock breeds, age, season, libido, and the variation in the condition of livestock (LukmanHy et al, 2022b).…”
Section: Resultscontrasting
confidence: 66%
“…What is meant by progressive motility is motility that moves nimbly, moves forward, can penetrate the ovum for fertilization, and also experiences a decrease because during the semen processing process there will be a decrease in sperm quality including motility. According to Rizal (2009), semen reservation can cause the death of spermatozoa, due to damage to the spermatozoa plasma membrane due to lipid/fat peroxidation and during the sperm sexing process this can result in damage to the plasma membrane. P2 and P3 treatment on day 7 and P2 can last until day 11 showing progressive motility ≥ 40% so that the semen can still be used for AI purposes, according to SNI standards that semen used for AI has at least progressive motility ≥ 40% (Yekti et al, 2018).…”
Section: Motilitymentioning
confidence: 99%
“…Upaya pemanfaatan spermatozoa yang berasal dari cauda epididimis saat ini telah dilakukan pada beberapa penelitian sebelumnya karena spermatozoanya memiliki potensi yang sangat baik untuk dipertahankan, seperti sapi Simmental memiliki viabilitas 78,83±6,83%, motilitas 72,25±9,11%, abnormalitas 11,00±1,26% (Satria et al, 2018), kerbau Rawa memiliki viabilitas ≥50%, motilitas ≥30% (Riyadhi et al, 2018) dan kambing Peranakan Ettawa (PE) memiliki motilitas 51,00±6,52%, viabilitas 72,00±0,84% (Rizal et al, 2016). Hasil yang diperoleh ini memberikan gambaran bahwa spermatozoa dari cauda epididimis masih memiliki kemampuan yang baik.…”
Section: Pendahuluanunclassified